2022
DOI: 10.1002/jmrs.584
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary interprofessional education using an online learning environment called values exchange: A qualitative investigation

Abstract: Introduction Interprofessional education (IPE) is implemented throughout the curricula of student healthcare professions as it is understood to provide positive impact on patient outcomes in the clinical environment. There are different methods to provide IPE such as through online learning or traditional face‐to‐face methods. However, there is a lack of research surrounding the use of Online Learning Environments (OLEs) to teach IPE. Methods In a pilot study, seventy‐one undergraduate radiography students and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Past literature reviews have highlighted the value students place on face-to-face interaction 10. This study's findings support that an interactive video conferencing platform can effectively provide the face-to-face learning experience that students value while increasing access across institutions and geography to IPE 28…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Past literature reviews have highlighted the value students place on face-to-face interaction 10. This study's findings support that an interactive video conferencing platform can effectively provide the face-to-face learning experience that students value while increasing access across institutions and geography to IPE 28…”
Section: Discussionsupporting
confidence: 70%
“…10 This study's findings support that an interactive video conferencing platform can effectively provide the face-to-face learning experience that students value while increasing access across institutions and geography to IPE. 28 The IPE simulation aimed to improve the students' awareness of each other's professional roles. Midwifery and OB-GYN residents indicated different levels of attainment of this aim.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are unique. While previous studies have exposed health professionals in nursing, radiology, pharmacy, and social care to the VX platform and determined it to be an effective tool for navigating ethical dilemmas and decision-making, [27][28][29][30][31][32] none have investigated its potential as an educational tool for promoting ethical research practices in public health among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…[43,44] Although we demonstrated the effect of the VX platform on public health research ethics, it is also applicable to any field of education and research, as shown in previous papers describing ethics in radiology. [31,32] It remains to be determined whether integrating strategic components of the learning environment that specifically address ethical uncertainty during undergraduate training would effectively prepare students for the pervasive uncertainty present in clinical practice. [45] Nonetheless, anticipation and preparation for uncertainty in clinical practice can enhance students self-efficacy when facing such unpredictability and promote their overall well-being.…”
Section: Practical Implicationsmentioning
confidence: 99%